2015
DOI: 10.1016/j.jcta.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting families of discrete structures are typically trivial

Abstract: The study of intersecting structures is central to extremal combinatorics. A family of permutations F ⊂ S n is t-intersecting if any two permutations in F agree on some t indices, and is trivial if all permutations in F agree on the same t indices. A k-uniform hypergraph is t-intersecting if any two of its edges have t vertices in common, and trivial if all its edges share the same t vertices. The fundamental problem is to determine how large an intersecting family can be. Ellis, Friedgut and Pilpel proved tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Frankl [22] proved the conjecture in the range n ≥ (2s − 1)k − s + 1, showing that the extremal families can be covered by s − 1 elements. Adapting the methods of Balogh et al [3], we show that a slightly larger lower bound on n guarantees that almost all families without a matching of size s have a cover of size s − 1. The s = 2 case corresponds to intersecting families.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Frankl [22] proved the conjecture in the range n ≥ (2s − 1)k − s + 1, showing that the extremal families can be covered by s − 1 elements. Adapting the methods of Balogh et al [3], we show that a slightly larger lower bound on n guarantees that almost all families without a matching of size s have a cover of size s − 1. The s = 2 case corresponds to intersecting families.…”
Section: Introductionmentioning
confidence: 75%
“…The s = 2 case corresponds to intersecting families. In this case, Balogh et al [3] showed that when n ≥ (3 + o(1))k, almost all intersecting families are trivial. Our final result improves the required bound on n to the asymptotically optimal n ≥ (2 + o(1))k. Indeed, when n = 2k, then the number of intersecting families is 3 1 2 ( n k ) = 3 ( n−1 k−1 ) , since we can freely choose at most one set from each complementary pair of k-sets {A, [n] \ A}.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that an example given by Frankl and Füredi [21] shows that this term cannot be reduced to below √ k. The problem of enumerating I 1 (n, k) was first investigated by Balogh, Das, Delcourt, Liu and Sharifzadeh [6]. Building on the of Balogh et al, Frankl and Kupavskii [22] and, independently, Balogh, Das, Liu, Sharifzadeh and Tran [7] established the asymptotic formula |I 1 (n, k)| = (n + o(1))2 ( n−1 k−1 ) for n ≥ 2k + 3 √ k ln k. Motivated by this result and the theorem of Ellis and Lifshitz, we make the following conjecture.…”
Section: Sets With Small Difference Constantmentioning
confidence: 99%
“…There are very few results in the case r ą 2 and ex r pn, Hq " opn r q. The only known case is when H consists of two edges sharing t vertices [1,4]. Very recently, Mubayi and Wang [8] studied |Forb r pn, Hq| when H is a loose cycle.…”
Section: §1 Introductionmentioning
confidence: 99%